Role of p63 isoform balance in recurrent nasal polyps. Issue 6 (2018) - Terrinoni, Alessandro; Palombo, Ramona; Pitolli, Consuelo; Caporali, Sabrina; Berardinis, Rita De; Ciccarone, Silvana; , Alessia; , Lanzillotta; Mauramati, Simone; Melino, Gerry; Bernardini, Sergio; Bruno, Ernesto
No abstract available